2017
DOI: 10.3390/f8040115
|View full text |Cite
|
Sign up to set email alerts
|

The Plight of Migrant Birds Wintering in the Caribbean: Rainfall Effects in the Annual Cycle

Abstract: Here, we summarize results of migrant bird research in the Caribbean as part of a 75th Anniversary Symposium on research of the United States Department of Agriculture Forest Service, International Institute of Tropical Forestry (IITF). The fate of migratory birds has been a concern stimulating research over the past 40 years in response to population declines documented in long-term studies including those of the IITF and collaborators in Puerto Rico's Guánica dry forest. Various studies indicate that in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Some other scholars also agree that vegetation cover and structure create substantial variations between avian communities of different habitats or land-use types. Have compared avian community assemblage and association of protected and unprotected montane grassland ecosystems in Bale Mountains National Park (BMNP) [98]. The report concluded that variations in avian communities between the two land-use types (protected and unprotected) are due to the difference in vegetation structure.…”
Section: Habitat and Seasonal Variationsmentioning
confidence: 99%
“…Some other scholars also agree that vegetation cover and structure create substantial variations between avian communities of different habitats or land-use types. Have compared avian community assemblage and association of protected and unprotected montane grassland ecosystems in Bale Mountains National Park (BMNP) [98]. The report concluded that variations in avian communities between the two land-use types (protected and unprotected) are due to the difference in vegetation structure.…”
Section: Habitat and Seasonal Variationsmentioning
confidence: 99%
“…The contrast between research effort for resident and migratory species is exemplified by the underrepresentation of the resident Parulidae species in this review. Migratory warblers, such as Kirtland's warbler, Setophaga kirtlandii, are one of the best studied groups in the Caribbean (Latta 2012), benefiting from attention and funding from North American researchers and programmes such as Partners in Flight (Wunderle and Arendt 2017). Globally, migrant bird species are proportionally overrepresented in the literature, both due to the ecological importance 1 3 of migratory behaviour and the geographic bias of research emanating from the global north (Ducatez and Lefebvre 2014).…”
Section: Which Species Are Studied?mentioning
confidence: 99%
“…Henareh et al [21], Gould et al [22], Feng at al. [23], Jennings et al [24], Van Beusekom et al [25,26] Monitoring of changes in biodiversity Campos-Cerqueira et al [27], Wunderle and Arendt [28], González et al [29], Heartsill-Scalley and González [30] Understanding novelty Lugo and Erickson [31] Attention to urban environments and their functioning Muñoz-Erickson et al [32] A social-ecological-technological focus Lugo and Alayón [33], Lugo [34] Fomenting collaboration among many sectors of society González and Heartsill-Scalley [35] Development of novel policies for effective governance McGinley [36], Rudel [37] Institutional improvement M. Rains [38] * Manuscripts are part of this Special Issue or are recent products of the Institute's program.…”
Section: Element Of Research or Action Contributed Manuscripts*mentioning
confidence: 99%